Screening primary sclerosing cholangitis and biliary dysplasia with endoscopic retrograde cholangiography and brush cytology: risk factors for biliary neoplasia - Boyd, Sonja; Tenca, Andrea; Jokelainen, Kalle; Mustonen, Harri; Krogerus, Leena; Arola, Johanna; Färkkilä, Martti A. (Endoscopy, 2016)
Background and study aims: Primary sclerosing cholangitis (PSC) is associated with increased risk of biliary dysplasia and cholangiocarcinoma (CCA). The aim of this study was to evaluate the role of early endoscopic retrograde cholangiography (ERC) with systematic brush cytology to identify risk factors associated with biliary neoplasia.Patients and methods: Patients who were referred for their first ERC for suspicion of PSC between January 2006 and October 2011 were included in the study. Brush cytology specimens were scored as benign, suspicious, or malignant. End points were CCA, biliary dysplasia, benign histology, or benign disease course for ≥ 2 years.Results: PSC was diagnosed in 261 patients (125 men, 136 women), most of whom were asymptomatic (n = 211). Cholangiographic changes were mild in 57.1 %. Men presented with advanced disease more often than women. Brush cytology was benign in 243, suspicious in 16, and malignant in 2 patients. Follow-up completed in 249 patients indicated a benign disease course in 232 patients. Seven patients were diagnosed with CCA and eight had biliary dysplasia in the explanted liver. Thus, 15 patients had biliary neoplasia, and suspicious or malignant brush cytology had been detected in 8 of them at initial brushing. Advanced extrahepatic cholangiographic changes with elevated aminotransferases at diagnosis seemed to be associated with increased risk of biliary neoplasia.Conclusions: Even in mostly asymptomatic patients with PSC, 42.9 % had advanced disease and 6.9 % presented with suspicious or malignant brush cytology at first ERC. Advanced extrahepatic ERC changes with elevated aminotransferases at diagnosis might be risk factors for biliary neoplasia.